2002
DOI: 10.1177/194589240201600105
|View full text |Cite
|
Sign up to set email alerts
|

Topical Antibiotic, Antifungal, and Antiseptic Solutions Decrease Ciliary Activity in Nasal Respiratory Cells

Abstract: This study was designed to investigate whether topical solutions, as they are used in the treatment of selected cases of rhinosinusitis, influence nasal mucociliary clearance. The objective of this study was to evaluate the effects of the following topical solutions on the ciliary beat frequency (CBF) of nasal respiratory cells: ofloxacin as an antibiotic; Betadine and hydrogen peroxide (H2O2) as antiseptic; and amphotericin B, itraconazole, and clotrimazole as antifungal solutions. Differences are described b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 7 publications
3
25
2
1
Order By: Relevance
“…275,283,284 There is also the potential for inducing fungal resistance due to the low concentrations used in topical formulations. Multiple trials used concentrations of amphotericin B at 100 µg/mL, a concentration that has been documented to not impede fungal growth in vitro compared with true inhibition at 200 and 300 µg/mL.…”
Section: Role Of Fungi In Crsmentioning
confidence: 99%
“…275,283,284 There is also the potential for inducing fungal resistance due to the low concentrations used in topical formulations. Multiple trials used concentrations of amphotericin B at 100 µg/mL, a concentration that has been documented to not impede fungal growth in vitro compared with true inhibition at 200 and 300 µg/mL.…”
Section: Role Of Fungi In Crsmentioning
confidence: 99%
“…Other studies have shown an impaired CBF in patients with allergic rhinitis or asthma 4, 5, 6, 7. Certain topical antibiotics have been shown to reduce the CBF and thus cannot be recommended in treatment of local infections 8. Pathogens targeting the airway like Pseudomonas aeruginosa , Streptococcus pneumoniae , or Haemophilus influenzae produce various cilio‐inhibitory factors 9, 10, 11, 12.…”
mentioning
confidence: 99%
“…Gosepath et al [19] studied whether antiseptic, antibiotic, and antifungal topical solutions (including amphotericin B) used in CRS treatment infl uence nasal mucociliary clearance by affecting the ciliary beat frequency (CBF) of nasal respiratory cells. In a prospective study, nasal respiratory cells were harvested from healthy individuals.…”
Section: Effect Of Amphotericin On Mucociliary Clearancementioning
confidence: 99%